Local recurrence of phyllodes tumors after surgery with wide compared to narrow margins: study protocol for a systematic review and meta-analysis - Carl Sars; Jan Frisell; Paul W. Dickman; Helena Sackey; Ebba K. Lindqvist (Systematic Reviews)
Abstract Background Phyllodes tumors are rare fibroepithelial breast lesions graded as benign, borderline, or malignant. Surgical resection with clear margins is the primary method of treatment. Consensus on margin width could prevent unnecessary large primary resections or reoperations, yet the optimal margins for different tumor grades remain unclear. This systematic review and meta-analysis will evaluate the effect of wide versus narrow margins on local recurrence rates after surgery for phyllodes tumors of the breast. In addition, the re-excision rates, adjuvant treatment and adverse events will be assessed. Methods An information specialist will assist in searching MEDLINE, EMBASE, Web of Science, Google Scholar, and Cochrane Library databases, as well as gray literature to identify randomized controlled trials, observational studies, and case series. Relevant abstracts from professional society meetings and web-based registries of clinical trials will also be included via hand-search and by forward-tracking papers and by searching the reference lists of the obtained articles. Studies included will compare patients, without age limitation, who were surgically treated for a histopathologically confirmed phyllodes tumor of the breast. Studies reporting both local recurrence rate and surgical excision margins will be included. No language restriction will be applied. Two reviewers will independently screen the titles and abstracts of the studies identified during the search using pre-defined inclusion criteria and data extraction from the full texts of selected studies will be performed. The quality of included studies will be assessed by two independent reviewers using the Cochrane Risk of Bias 2.0 tool for randomized trials, the Newcastle–Ottawa Scale for observational studies and the Joanna Briggs Institute Checklist for case series. A meta-analysis on pooled local recurrence rates will be conducted, stratified by different phyllodes tumor grades and surgical margins. Discussion This systematic review will provide a synthesis of current evidence on the optimal surgical margins of phyllodes tumors and its effect on local recurrence rates. These findings aim to provide clinicians with guidelines and to establish a strong research base for future studies in this field. Trial registration PROSPERO CRD420250640098.